Tuvalu : Early Childhood Development - World Bank (Washington, DC, 2015)
This report presents an analysis of the early childhood development (ECD) programs and policies which affect young children in Tuvalu and recommendations to move forward. It is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER)-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Tuvalu, along with some regional and international comparisons.